Selective light absorber-assisted single nickel atom catalysts for ambient sunlight-driven CO2 methanation - Yaguang Li (Nature Portfolio, 2019)
While light-driven CO2 methanation provides a renewable means to upgrade waste emissions, the sunlight is insufficient to drive high temperature CO2 methanation. Here, authors prepare single-atom Ni on Y2O3 with a selective light absorber for ambient-sunlight-driven photothermal CO2 methanation.